Field game-based learning as an integrative approach to motor competence in elementary school children: a pre-experimental study - Soemardiawan; Primayanti, Intan; Gustian, Uray (Edu Sportivo: Indonesian Journal of Physical Education, 2026)
Background: Motor competence is a key component of physical education, integrating motor skill proficiency and game understanding. However, instructional approaches often separate technical skill development from its contextual application, limiting students’ holistic competence development. Objectives: This study aimed to examine the preliminary effects of a field game-based learning approach on elementary school students’ motor competence. Methods: A pre-experimental one-group pretest–posttest design was employed with 12 elementary school children. Motor skills were assessed using the Test of Gross Motor Development-2 (TGMD-2), while game understanding was measured using the Game Performance Assessment Instrument (GPAI). Data were analysed using paired-sample t-tests and Cohen’s d effect size. Results: The results indicated a statistically significant improvement in motor competence (t = 2.81, p = 0.017), with a large effect size (d = 0.81). Improvements were observed in both motor skill execution and decision-making aspects of game performance. Conclusion: Field game-based learning demonstrates potential as an integrative approach to enhancing motor competence by combining physical and cognitive learning components. However, given the pre-experimental design and small sample size, the findings should be interpreted as preliminary. Further research using more rigorous experimental designs is recommended.